1999
DOI: 10.1073/pnas.96.7.3664
|View full text |Cite
|
Sign up to set email alerts
|

Spin-lattice relaxation of laser-polarized xenon in human blood

Abstract: The nuclear spin polarization of 129 Xe can be enhanced by several orders of magnitude by using optical pumping techniques. The increased sensitivity of xenon NMR has allowed imaging of lungs as well as other in vivo applications. The most critical parameter for efficient delivery of laser-polarized xenon to blood and tissues is the spin-lattice relaxation time (T 1 ) of xenon in blood. In this work, the relaxation of laser-polarized xenon in human blood is measured in vitro as a function of blood oxygenation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 25 publications
(33 reference statements)
8
75
1
Order By: Relevance
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…In the bloodstream, dissolved HP 129 Xe is transported to distal organs by the systemic blood circulation. The longitudinal relaxation time T1 of HP 129 Xe in the human blood is sufficiently long (6 s to 8 s for arterial‐oxygenated blood and 3 s to 4 s for venous‐deoxygenated blood) for it to be detected in the distal organs 10, 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that under the conditions of their experiment (e.g., xenon dissolved in rat blood in vivo at 37 "C and 2 T) the xenon exchange between RBCS and plasma was contrast to the previous in vitro fast with respect to the the NMR time scale, in results involving xenon in human blood at higher fields and ambient conditions [224,225]. Indeed, this result is particularly surprising considering the new results of Bifone and co-workers [132], where the xenon exchange in human blood was still slow on the NMR time scale even though the experiments CSI experiments could become a powerful diagnostic tool, permitting lung ventilation and perfusion to be studied simultaneously.…”
Section: Enhanced Nmr and Mri Of Tissues 210contrasting
confidence: 52%
“…Xenon has been shown to bind to various proteins in crystals and in solution [66,125,126,81,127,128,129,130,131,132]. The formation of xenon clathrates has also been investigated extensively with both thermally polarized and laser-polarized xenon (see for example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have exploited sensitive xenon chemical shifts to characterize the interactions between xenon and organic compounds such as ␣-cyclodextrin (5) and cryptophane-A (6), the membrane protein channel gramicidin (7), and the globular proteins myoglobin and hemoglobin (8). In addition, it has been shown that the 129 Xe spin-lattice relaxation time (T 1 ) is reduced dramatically when xenon comes into contact with cyclodextrins (9), lipids (10), and proteins in blood (11)(12)(13)(14)(15). Recent advances in optical pumping technology (16) have further motivated such studies of xenon-molecule interactions by providing 129 Xe NMR signal enhancements of up to five orders of magnitude (17).…”
mentioning
confidence: 99%